MAKNA KEHIDUPAN KEKAL DALAM MATIUS 19: 16-26 DAN RELEVANSINYA TERHADAP ORANG MUDA KATOLIK - Ratrigis, Ayus (Jurnal Euntes, 2023)
Abstract Eternal life is always coveted by every believer. Awareness regarding eternal life needs to be given to every believer, especially young people. The story of the youth presented by Jesus in Matthew 19:16-26 displays two meanings regarding eternal life, namely the quality of life and God's grace. For life to gain eternity, the thing that needs to be done is to have the courage to let go of the attachments or attachments that exist in every young person. By letting go of attachments to young people, they can improve their quality of life. Therefore, by the mercy of God they can obtain eternal life.   Abstrak Kehidupan kekal selalu didambakan oleh setiap umat beriman. Kesadaran mengenai kehidupan kekal perlu diberikan kepada setiap umat beriman, khususnya orang muda. Kisah orang muda yang ditampilkan oleh Yesus dalam Matius 19:16-26 menampilkan dua makna mengenai kehidupan kekal yaitu kualitas hidup dan kemurahan Allah. Untuk memperoleh kehidupan kekal itu hal yang perlu dilakukan ialah berani melepaskan kelekatan atau keterikatan yang ada pada diri setiap orang muda. Dengan melepaskan kelekatan pada diri orang muda, mereka dapat meningkatkan kualitas hidup mereka. Dengan demikian, berkat kemurahan Allah mereka dapat memperoleh kehidupan kekal.